Filsafat Kenabian Muhammad Saw. di dalam al-Quran - Hakam al-Ma'mun (MAGHZA, 2021)
The discussion of Prophetic philosophy was one of the central themes for Muslim philosophers in the Middle Ages. This is because one of the foundations of the Muslim faith is built on trust in God's messengers as recipients and transmitters of divine messages. Therefore, if someone has claimed to be a believer, the consequence that must be accepted is to believe in the existence of Muhammad's prophecy. However, history records the existence of some groups of Muslims in the Middle Ages that have ruled out the role of a prophet. The assumption that underlies them solely rests on the role of human reason which is considered sufficient to lead him to the truth so that the role of prophethood is no longer needed. This paper highlights how the Qur'an explains the concept of Muhammad's prophecy with all the visions and missions it carries. The Qur'an through sura al-Ahzab verses 45-46 has captured some of the prophetic characteristics of Muhammad. The philosophical approach in this research is a concrete effort to understand and explain religious doctrine more logically and systematically. The results of this study indicate that sura al-Ahzab verses 45-46 contain the prophetic message of Muhammad's prophethood, that is his testimony as a messenger who brings good news as well as a warning to people who are in denial of the existence of God. In addition, Muhammad also played a role as a caller for truth and a guide for lost mankind.